Where the truth lies - Egoyan, Atom, 1960-; Bacon, Kevin, 1958-; Firth, Colin, 1960-; Lohman, Alison, 1979-; Danna, Mychael; Chaykin, Maury; Holmes, Rupert; Telefilm Canada; Thinkfilm (Firm); Serendipity Point Films; Sony Pictures Home Entertainment (Firm) (Culver City, CA : Sony Pictures Home Entertainment, 2006)
Karen O'Connor, a young journalist known for her celebrity profiles, is consumed with discovering the truth behind a long-buried incident that affected the lives and careers of showbiz team Vince Collins and Lanny Morris.
Title from container.
Based on the novel by Rupert Holmes.
Originally released as a motion picture in 2005.
Special features: Deleted scenes; "The making of 'Where the truth lies.'"
Director of photography, Paul Sarossy ; editor, Susan Shipton ; music, Mychael Danna ; costume designer, Beth Pasternak ; production designer, Phillip Barker.
Kevin Bacon, Colin Firth, Alison Lohman, David Hayman, Rachel Blanchard, Maury Chaykin, Kristin Adams.
Keywords: Holmes, Rupert -- Film and video adaptations; Entertainers -- United States -- Drama; Women journalists -- United States -- Drama; Murder -- Investigation -- United States -- Drama; Feature films; Detective and mystery films; Video recordings for the hearing impaired; Mystery -- Feature; Thriller -- Feature; Mystery films; Suspense films